2‐oxoglutarate modulates the affinity of FurA for the ntcA promoter in Anabaena sp. PCC 7120. Issue 2 (29th September 2019) - Guío, Jorge; Sarasa‐Buisan, Cristina; Velázquez‐Campoy, Adrián; Bes, María Teresa; Fillat, María F.; Peleato, María Luisa; Sevilla, Emma
Abstract : 2‐oxoglutarate (2‐OG) is a central metabolite that acts as a signaling molecule informing about the status of the carbon/nitrogen balance of the cell. In recent years, some transcriptional regulators and even two‐component systems have been described as 2‐OG sensors. In the nitrogen‐fixing cyanobacterium Anabaena sp. PCC 7120, two master regulators, NtcA and FurA, are deeply involved in the regulation of nitrogen metabolism. Both of them show a complex intertwined regulatory circuit to achieve a suitable regulation of nitrogen fixation. In this work, 2‐OG is found to bind FurA, modulating the specific binding of FurA to the ntcA promoter. This study provides evidence of a new additional control point in the complex network controlled by the NtcA and FurA proteins. Abstract :